2016
DOI: 10.4103/0971-5916.191792
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of APC in the molecular pathogenesis of gallbladder cancer

Abstract: Background & objectives:Loss of function of adenomatous polyposis coli (APC) has been reported in cancer. The two promoters of APC, 1A and 1B also have roles in cancer. But, the epigenetic role of APC promoters is not yet clear in gallbladder cancer (GBC) and gallstone diseases (GSD). We undertook this study to determine the epigenetic role of APC in GBC and GSD.Methods:Methylation-specific (MS)-PCR was used to analyze the methylation of APC gene. The expression of APC gene was studied by semi-quantitative PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…This list includes well-known oncogenes, CTNNB1, ERBB2, ERBB3, KRAS, PIK3CA, BRAF , and NFE2L2 , tumor suppressors, TP53, ARID2, STK11, CDKN2A, SMAD4, SMARCA4, ARID1A, APC, NF1 , and MAP2K4 , and less well-established cancer-associated genes such as ELF3, EHF, ACVR2A, PSIP1, CHRM3, HIST1H2AG, KAT8 , and ZNF107 . Previous studies on GBC reported TP53, KRAS and ERBB3 as significantly mutated GBC genes (SMG) 6 , though low-frequency mutations were observed in other SMG GBC genes reported in this study 6 , 7 , 20 .
Fig.
…”
Section: Resultscontrasting
confidence: 60%
“…This list includes well-known oncogenes, CTNNB1, ERBB2, ERBB3, KRAS, PIK3CA, BRAF , and NFE2L2 , tumor suppressors, TP53, ARID2, STK11, CDKN2A, SMAD4, SMARCA4, ARID1A, APC, NF1 , and MAP2K4 , and less well-established cancer-associated genes such as ELF3, EHF, ACVR2A, PSIP1, CHRM3, HIST1H2AG, KAT8 , and ZNF107 . Previous studies on GBC reported TP53, KRAS and ERBB3 as significantly mutated GBC genes (SMG) 6 , though low-frequency mutations were observed in other SMG GBC genes reported in this study 6 , 7 , 20 .
Fig.
…”
Section: Resultscontrasting
confidence: 60%